Evaluation of spatio-temporal variations of FVC and its relationship with climate change using GEE and Landsat images in Ganjiang River Basin. Issue 26 (13th December 2022) - Fu, Bolin; Yang, Wenlan; Yao, Hang; He, Hongchang; Lan, Guiwen; Gao, Ertao; Qin, Jiaoling; Fan, Donglin; Chen, Zhikun
Abstract: Fractional vegetation cover (FVC) is an important feature of the ecosystem, and continuous evaluation of vegetation status is one of the key issues in the ecological monitoring of river basins. This article divided the Ganjiang River Basin (GRB) into 73 subbasins, and quantitatively evaluated the spatio-temporal FVC changes at multiple scales from 2000 to 2019 using Google Earth Engine and Landsat series images. Theil-Sen slope estimator and Mann-Kendall algorithm were used to monitor the spatio-temporal change trend of the FVC in the basin and subbasins, respectively. Mann-Kendall test was executed to analyze the abrupt change of FVC. Hurst exponent and Theil-Sen Slope were integrated to evaluate the consistency of FVC change and predict its spatio-temporal evolution trend. Grey correlation analysis and Pearson correlation analysis were selected to quantify the relationship between FVC and terrain, climate factors in each subbasin, and further explore the effect of single factor and multiple-factor combination on FVC change. The results showed that: (1) FVC in the GRB was in good condition, and increased with the elevation and slope, but the FVC in the subbasins with elevation less than 200 m ranged from 25.95% to 72.86%. From 2000 to 2019, the area of high coverage increased significantly compared with other coverage grades. The FVC of most subbasins varied from 45% to 80%, and the change range fluctuated from 9.4% to 36.53%. (2) The FVC has presented a fluctuating growth trend in the past 20 years. The area with increasing FVC reached 68.93%, and the area of a significant improvement in FVC was 11.65% more than the area with the significant degradation. The FVC in the 64.38% of subbasins has abrupt changed, and 20.55% of subbasins has changed dramatically with 7 abrupt change points, which demonstrated that the subbasin-scale abrupt change analysis could accurately monitor the spatio-temporal change of FVC. (3) The 76% of basin appeared the weak consistency in the FVC, and the northern and southern of the basin present a trend of degradation in the future. (4) The spatio-temporal distribution of FVC in GRB was greatly affected by terrain. The effect of temperature and relative humidity on the FVC change was greater than that of precipitation. The synergistic effect of three climatic factors on FVC change was more significant than that of a single factor.